How can coworking spaces promote knowledge sharing among coworkers: an identification-based perspective - Tandon, Ankita; Chakrabarti, Diganta (Development and learning in organizations, 2025)
Purpose Coworking spaces provide coworkers significant opportunities to connect, share knowledge, learn from each other and innovate. Yet, there is hardly any research literature on how coworking spaces support this. This paper examines how coworking spaces can promote knowledge sharing among coworkers to support innovation and develops a conceptual framework for the same. Design/methodology/approach This paper brings together literature from the fields of coworking spaces, communities of practice, identification and knowledge sharing to develop a conceptual framework. Findings Coworking space managers can drive specific activities to promote a sense of community among coworkers. This can create identification with the coworking community and with the coworking space, leading to higher propensity to collaborate, share knowledge and work together to innovate. Research limitations/implications This paper proposes a conceptual framework that can be further examined through qualitative and quantitative research. Practical implications This paper suggests specific activities which coworking space managers can undertake to promote learning and innovation – important motivations for people to use coworking spaces. This will also help coworking spaces to make a strong business case and differentiate themselves from competitors. Originality/value Since coworking spaces bring together people from varied backgrounds who belong to diverse organizations and work on varied domains, nudging them to share knowledge is difficult. This paper is one of the first attempts at developing a framework to promote knowledge sharing in coworking spaces.